The effects of music preference and exercise intensity on psychological variables. - Dyrlund AK; Wininger SR; Dyrlund, Allison K; Wininger, Steven R (Journal of Music Therapy)
The purpose of this study was to examine the effects of music preference and exercise intensity on exercise enjoyment, perceived exertion (RPE), and attentional focus. Participants were assigned to 1 of 3 music preference conditions (most preferred, least preferred, or no music) and walked/ran on a treadmill at 1 of 3 exercise intensities (low, moderate, or high) for 20 minutes. Measures of exercise enjoyment, RPE, and attentional focus (association, dissociation, distress) were taken. A 3 x 3 ANOVA on enjoyment revealed that when participants paid attention to the music, music accounted for roughly 5% of the variance in exercise enjoyment (p = .04). Results of a 3 (music) x 3 (intensity) repeated measures ANOVA on RPE showed a main effect of intensity (p < .001) but no main effect for music and no interaction effect. A 3 x 3 ANOVA on attentional focus revealed that those in the high intensity condition reported the greatest association (p < .001) and distress (p < .001). Although not significant, on average, participants in the most preferred music condition reported the highest levels of dissociation.